B cell maturation antigen (BCMA)-based immunotherapy for multiple myeloma. (2nd November 2019) - Tai, Yu-Tzu; Anderson, Kenneth C
ABSTRACT: Introduction : B cell maturation antigen (BCMA) contributes to MM pathophysiology and is a target antigen for novel MM immunotherapy. Complete responses have been observed in heavily pretreated MM patients after treatment with BCMA antibody-drug conjugates (ADC), chimeric antigen receptor T, and bi-specific T cell engagers (BiTE®). These and other innovative BCMA-targeted therapies transform the treatment landscape and patient outcome in MM. Areas covered : The immunobiological rationale for targeting BCMA in MM is followed by key preclinical studies and available clinical data on efficacy and safety of therapies targeting BCMA from recent phase I/II studies. Expert opinion : BCMA is the most selective MM target antigen, and BCMA-targeted approaches have achieved high responses even in relapse and refractory MM as a monotherapy. Long-term follow-up and correlative studies using immuno-phenotyping and -sequencing will delineate mechanisms of overcoming the immunosuppressive MM bone marrow microenvironment to mediate additive or synergistic anti-MM cytotoxicity. Moreover, they will delineate cellular and molecular events underlying the development of resistance underlying relapse of disease. Most importantly, targeted BCMA-based immunotherapies used earlier in the disease course and in combination (adoptive T cell therapy, mAbs/ADCs, checkpoint and cytokine blockade, and vaccines) have great promise to achieve long-term disease control and potential cure.